2022
DOI: 10.1186/s13046-021-02213-0
|View full text |Cite
|
Sign up to set email alerts
|

Chloride intracellular channel 1 activity is not required for glioblastoma development but its inhibition dictates glioma stem cell responsivity to novel biguanide derivatives

Abstract: Background Chloride intracellular channel-1 (CLIC1) activity controls glioblastoma proliferation. Metformin exerts antitumor effects in glioblastoma stem cells (GSCs) inhibiting CLIC1 activity, but its low potency hampers its translation in clinical settings. Methods We synthesized a small library of novel biguanide-based compounds that were tested as antiproliferative agents for GSCs derived from human glioblastomas, in vitro using 2D and 3D cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…In a recent publication, we demonstrated the existence of GBM subsets whose aggressiveness is unrelated to CLIC1 expression whereas displaying resistance towards metformin treatment 42 . This introduces the possibility to establish novel eligibility criteria for discriminating patients' cohorts in a personalized trial setting based on CLIC1 expression.…”
Section: Discussionmentioning
confidence: 85%
“…In a recent publication, we demonstrated the existence of GBM subsets whose aggressiveness is unrelated to CLIC1 expression whereas displaying resistance towards metformin treatment 42 . This introduces the possibility to establish novel eligibility criteria for discriminating patients' cohorts in a personalized trial setting based on CLIC1 expression.…”
Section: Discussionmentioning
confidence: 85%
“…3 G). The most highly connected gene in this module is CLIC1, a chloride ion channel with high expression and potential therapeutic and prognostic value in adult glioma [ 39 , 40 ]. Our work links CLIC1 expression with EGFR activity in LGG.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, several novel SDH inhibitors have been identified using in silico library design which can be potentially utilised in future studies (60). Interestingly, CLIC1 inhibitors has also been explored in glioblastoma cells and found that inhibition of CLIC1 sensitizes glioblastoma stem cells by inhibiting proliferation, migration, invasiveness and self-renewable in vitro and in vivo (61)(62)(63). Along with this, using transcriptomic profile of patients with high and low risk score, drug sensitivity assay using FDA approved drugs can be performed to identify drugs precise targeted therapy for patients with high-risk score in future studies (64)(65)(66).…”
Section: Discussionmentioning
confidence: 99%